2009
DOI: 10.1186/1471-2164-10-619
|View full text |Cite
|
Sign up to set email alerts
|

The expansion of amino-acid repeats is not associated to adaptive evolution in mammalian genes

Abstract: BackgroundThe expansion of amino acid repeats is determined by a high mutation rate and can be increased or limited by selection. It has been suggested that recent expansions could be associated with the potential of adaptation to new environments. In this work, we quantify the strength of this association, as well as the contribution of potential confounding factors.ResultsMammalian positively selected genes have accumulated more recent amino acid repeats than other mammalian genes. However, we found little s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 49 publications
(78 reference statements)
0
8
0
Order By: Relevance
“…For example, Cruz et al . 45 suggested that hydrophobic and acidic amino acids are more likely to be used in LCRs compared to amino acids belonging to other Lehninger categories. However, our results do not show this preference as Asn and Lys belong to the “polar uncharged” and “basic” categories, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Cruz et al . 45 suggested that hydrophobic and acidic amino acids are more likely to be used in LCRs compared to amino acids belonging to other Lehninger categories. However, our results do not show this preference as Asn and Lys belong to the “polar uncharged” and “basic” categories, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The causal factors underlying this variation are still a matter of dispute [13,17], and some have attributed them to GC content bias [16,18,23]. In plants, repetitive DNA is widely used as a genetic marker, and its variation among transcripts has been observed [24].…”
Section: Introductionmentioning
confidence: 99%
“…This AAR was suggested to control circadian period length [ 12 ]. Large-scale analyses indicate that AARs tend to participate in the regulation of transcription [ 8 , 13 , 14 ] and are frequently involved in protein-protein interactions [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Finding more glutamine than any other amino acid in repeats despite using a criterion that sampled far fewer repeats, i.e. less than 25% of repeats have 9 or more codons in Drosophila [ 46 , 47 ], suggests that glutamine may be particularly prone to repeat formation in flies. Indeed, Faux et al [ 28 ] found that glutamine was also the most common amino acid among repeats in Anopheles gambiae , although it was only 1/6 as common as in D. melanogaster .…”
Section: Discussionmentioning
confidence: 99%